Old Pastor and Local Bureaucrats: Recasting Church-State Relations in Contemporary China. (September 2019) - Liu, Jifeng; White, Chris
In examining the relationships between a state-recognized Protestant pastor and local bureaucrats, this article argues that church leaders in contemporary China are strategic in enhancing interactions with the local state as a way to produce greater space for religious activities. In contrast to the idea that the Three-Self church structure simply functions as a state-governing apparatus, this study suggests that closer connection to the state can, at times, result in less official oversight. State approval of Three-Self churches offers legitimacy to registered congregations and their leaders, but equally important is that by endorsing such groups, the state is encouraging dialogue, even negotiations between authorities and the church at local levels.